Perceptual space and adjective rating of 2.5D tactile patterns - Inwook Hwang; Sungryul Yun; Jaeyoung Park (Scientific Reports)
Abstract The present study investigates the human haptic perception of 2.5D tactile patterns based on adjective ratings and how physical factors, such as the bump diameter of the pattern or material, affect their tactile perception. We designed fifty tactile patterns by varying the pattern’s bump diameter, pattern uniformity, and material and evaluated the effect of the parameters on haptic perception by conducting a couple of human subject experiments. In Experiment 1, the perceived intensities of the tactile patterns were tested for a total of ten properties (adjective pairs). The experimental results indicate significant effects of the factors, the bump diameter, pattern type, and material on the perceived intensities of the 2.5D patterns. In Experiment 2, a cluster sorting of the tactile patterns was conducted, and a haptic perceptual space was constructed with an MDS (multi-dimensional scaling). The results indicate a grouping of the samples by bump diameter and an effect of sample pattern uniformity for larger 2.5D tactile patterns. Overall, the present study showed that bump diameter, pattern type, and material significantly affected the perception of 2.5D tactile patterns based on the adjective ratings, and the 2.5D patterns could be grouped by the pattern’s bump diameter and uniformity.